BREASTFEEDING, CARE, MOTHERHOOD: REGULATIONS, NEEDS AND SUBJECTIVITIES - Marcela Komechen Brecailo; Marlene Tamanini (Universidade do Estado do Rio de Janeiro, 2016)
This article aims to analyze aspects of breastfeeding experience in relation to daily life and the institutionalized discourse on breastfeeding, as well as other speeches. It is a qualitative research with in-depth analysis of content held in 12 women interviews, mothers of 6 months to two years children. The analysis concerns to: the recommendation and the value given to the institutionalized knowledge; the incidence of medical discourse on women's practice; autonomy, interpretation and possibilities facing other women speeches; the daily organization on breastfeeding situation; and experiences with weaning. Many are the ways found by these women to address the requirements with breastfeeding in their daily lives and to accept or not the medical discourse. It is the experience, current or former, that forces them to confront or confirm this discourse, establishing their own feeding and nutrition ideal, according to what better suits to their own needs. They also consider the experience of their relatives that already are mothers, how the child reacts, and the compatibility of breastfeeding requirements with their needs and other activities. The analysis showed that are desired and necessary measures to support breastfeeding, listening to the women experiences and their needs, and equal participation in support care policies, as well as sharing of other tasks among family members as democracy of care strategy construction. DOI: 10.12957/demetra.2016.22507